A web app-based music intervention reduces experimental thermal pain: A randomized trial on preferred versus least-liked music style - Soyeux, Orelle; Marchand, Serge (Frontiers in Pain Research, 2023)
Digital technologies and emerging innovations are increasingly being used to strengthen national health systems. Music is used as a management technique for pain in multiple clinical settings. The objective of this study is to demonstrate the effects of a web app-based music intervention on pain. The participants were healthy adults and underwent three conditions: Conditioned Pain Modulation (CPM), Most-Liked Music (MLM) and Least-Liked Music (LLM). The music used is MUSIC CARE©, a web app-based personalized musical intervention used in clinical settings. Pain was measured before starting the 20-minute music intervention and after three times points for each music condition: 2.20 minutes, 11.30 minutes, and 20 minutes. Mean pain perceptions were significantly reduced under both LLM and MLM conditions. Pain decrease was more important under MLM condition than LLM condition at 2.20 minutes with a mean difference between both conditions of 9.7 (±3.9) (p=0.0195) and at 11.30 minutes (9.2 (±3.3), p=0.0099). LLM is correlated with CPM but not MML, suggesting different mechanisms between LLM and MLM. Musical intervention, a simple method of application, fits perfectly into a multidisciplinary global approach and helps to treat the pain and anxiety disorders of participants.